PERSEPSI MASYARAKAT MUSLlM TENTANG ZAKAT DI KOTA PALU - Attamimi, Faisal (Hunafa: Jurnal Studia Islamika, 2008)
The purpose of this study was to analyze the perception of Muslim society of PaluÂ  toÂ  dhakÃ¢h. The method employed in this reserach was qualitative one. The teachniques of data collection employed was observation, interview and questionaire. The results of this research indicated that most ofÂ  Muslims ofÂ Â  PaluÂ  percieved dhakÃ¢h as being an indivudual ibÃ¢dah so that they preferred distributing their dhakÃ¢h Â individually to distributing it throughÂ  the BAZ (The Office of Collector and Distributor of Alms-Giving). The BAZ ofÂ  Palu could not be optimally managed because of (1) the lack of human resources; (2) the lack of Muslimsâ knowledge of Palu about the essence of dhakÃ¢h, and (3) the ineffectiveness of dhakÃ¢h management of Â the BAZ of Palu.Kata Kunci: persepsi, masyarakat muslim, Â zakat, Â Badan Amil Zakat